Anticancer Potential of Pulicaria crispa Extract on Human Breast Cancer MDA-MB-231 Cells - Barnawi, Ibrahim O.; Ali, Imran (Letters in Drug Design & Discovery, 2019)
Background: Breast cancer is the common cause of deaths among women globally with 15% mortality globally. Introduction: Today, about 80% of the rural population depends on natural products as primary health care. Pulicaria crispa (L., family Compositae) is utilized in traditional medicine for curing colds, coughs, colic, and excessive sweating and as a carminative. Methods: The extracts of Pulicaria crispa; grown in Saudi Arabia; were assessed to measure the cytotoxicity with MDA-MB-231 breast cancer cell lines. Soxhlet extraction was utilized for stem, leaves and flower with 70% ethanol. The cytotoxicity of the extracts with MDA-MB-231 breast cancer cells was evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) assays. Results: The apoptotic cellular morphological alterations were detected by fluorescence microscopes. The results indicated that Pulicaria crispa exhibited a strong anticancer activity with a halfmaximal inhibitory concentration (IC50) of 180 μg/mL against breast cancer cells. The loss in cell integrity, shrinkage of cytoplasm, and cell detachment were seen in the extract treated with MDAMB- 231 cells. The cell death was due to membrane destruction. Conclusion: Pulicaria crispa extracts indicated significant cytotoxicity against human breast cancer cells (MDA-MB-231 cells). The extract of this plant may be given to the patients having breast cancer.
Keywords: cytotoxicity